2018
DOI: 10.1002/star.201700278
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Environment and Genotype‐by‐Environment Interaction on Functional Properties of Amylose‐Free and Wildtype Cassava Starches

Abstract: Ten and thirty cassava genotypes producing wildtype and amylose‐free (waxy) starch respectively, are grown at low (LA) and intermediate (IA) altitudes (<213 and >900 m above sea level (m.a.s.l.) respectively). The functional properties of the starch from these materials are analyzed. The relative importance of environment, clones (within starch type) and genotype‐by‐environment interaction (GxE) is assessed through an analysis of variance. GxE effects are non‐significant, whereas environment and clones (within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…GxE interactions are widely reported to influence a variety of traits of cassava genotypes across contrasting agro-ecological environments ( Esuma et al 2016 ; Fotso et al 2018 ), with the consequence that cultivars are often recommended for specific regions within countries. There are exceptions to this general theme within the published literature on cassava, however, and some studies have demonstrated the absence of GxE interactions for traits such as yield ( Tumuhimbise et al 2014 ) and starch quality ( Karlström et al 2019 ). The lack of a significant GxE interaction with respect to yield in our study is likely to be a consequence of multiple factors being associated with environment differences.…”
Section: Discussionmentioning
confidence: 98%
“…GxE interactions are widely reported to influence a variety of traits of cassava genotypes across contrasting agro-ecological environments ( Esuma et al 2016 ; Fotso et al 2018 ), with the consequence that cultivars are often recommended for specific regions within countries. There are exceptions to this general theme within the published literature on cassava, however, and some studies have demonstrated the absence of GxE interactions for traits such as yield ( Tumuhimbise et al 2014 ) and starch quality ( Karlström et al 2019 ). The lack of a significant GxE interaction with respect to yield in our study is likely to be a consequence of multiple factors being associated with environment differences.…”
Section: Discussionmentioning
confidence: 98%
“…Gu et al (16) reported that ambient temperature 3 months before cassava harvesting was positively correlated to paste clarity and pasting temperature but negatively correlated to freeze-thaw stability of cassava flour. Moreover, Karlström et al (17) found that peak viscosity of cassava starch is statistically higher in plants grown in low altitude compared with those grown in intermediate altitude. These studies mainly focused on the effect of environmental factors on functional properties of starch.…”
Section: Introductionmentioning
confidence: 99%
“…The highland variety Cumbre3 provided the best results from non-waxy starches, particularly for the evaluation conducted in 2013. Different batches (years 2013, 2015A and 2015B) resulted in distinctive performances, suggesting that environmental and biological conditions during plant growth have strong effects as reported by Karlström 48 on waxy cassava starch and on cassava landrace starches. 49,50…”
Section: Resultsmentioning
confidence: 73%
“…S1 †). 48 on waxy cassava starch and on cassava landrace starches. 49,50 By and large, responses to fermentation from each source of starch could be reliably summarized using data from 10 days of fermentation, which is a useful reference time in relation to commercial production of fermented starches.…”
Section: Breadmaking Potentialmentioning
confidence: 99%